DESAINER DENGAN MANAJEMEN YANG HAIR - Taswadi Taswadi (Jurnal Dimensi Seni Rupa dan Desain, 2008)
AbstractThis book aims to assist the achievement of good results from design.Two main concerns in this book have predominated. First concern, to identijy the management issues and responsibih'ties judged to be mos.t sigm_ficant in influencing the progress and outcomes of design projects. Second, to provide information about appropriate management methods and approaches. It does not to set out to influence how designers use their skills. Even less does it attempt to turn managers into designers. It may lead to a better understanding of what designers actually do. It contains a cross- section of views and advice from more than 40 contributor writers. All expert in design fields AbstrakBuku "Design Management; A Handbook of Issues and Methods ", bertujuan untuk memberi basil terbaik desain dari aspek manajemen. Terdapat dua perhatian utama dari buku ini. Pertama, melakukan identifikasi isu-isu manajemen dan bertanggungjawab dalam memberi penilaian pada kemajuan dan basil proyek desain. Kedua, untuk menyediakan informasi tentang metode manajemen dan pendekatan yang tepat. Buku ini tidak bertujuan untuk mempengaruhi bagaimana desainer dalam memakai ketrampilan yang telab dimiliki. Juga tidak